1991
DOI: 10.1016/0166-9834(91)80090-j
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized tetragonal zirconium oxide as a support for catalysts Evolution of the texture and structure on calcination in static air

Abstract: Single-phase tetragonal zirconium oxides have been made by the incorporation of 5.4 mol-% of Y3+ or La3+ in ZIG, to form solid solutions Tbe samples were prepared by controlled coprecipitation from aqueous solutions of the respective metal chlorides at room temperature and at a constant pH of 10, followed by calcination at 500°C (in the case of the Y3+-doped sample) or 600" C (in the case of the La3+ -doped sample) to effectuate the crystallization into the tetragonal phase. The process of crystallization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
5

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(65 citation statements)
references
References 34 publications
5
51
0
5
Order By: Relevance
“…Yamamoto et al [24] reported that the tetragonal ZrO 2 phase shows a strong Raman band at 263 cm´1 and several other bands at 148, 325, 472, 608 and 640 cm´1. On other hand, the monoclinic ZrO 2 phase shows strong bands at 173, 185 and 472 cm´1 and some other bands at 140, 216, 260, 301, 328, 342, 500, 553 and 632 cm´1 [25]. The Raman spectra for all the samples are shown in Figure S1 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamamoto et al [24] reported that the tetragonal ZrO 2 phase shows a strong Raman band at 263 cm´1 and several other bands at 148, 325, 472, 608 and 640 cm´1. On other hand, the monoclinic ZrO 2 phase shows strong bands at 173, 185 and 472 cm´1 and some other bands at 140, 216, 260, 301, 328, 342, 500, 553 and 632 cm´1 [25]. The Raman spectra for all the samples are shown in Figure S1 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…553 and 632 cm −1 [25]. The Raman spectra for all the samples are shown in Figure S1 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…1. The peaks that appeared at the angle 2h 5 30.2u, 50.3u, 59.8u are assigned to the tetragonal phase [11]. The figure reveals a well-crystallized tetragonal phase.…”
Section: Resultsmentioning
confidence: 91%
“…These results indicate that the Al 2 O 3 diffusion barrier suppresses the sintering of ZrO 2 particles after not only the final calcination at 900 • C but also higher temperature durability test (1000 • C) and the barrier in A80ZL most effectively inhibit the crystallite growth of ZrO 2 . Since pure ZrO 2 prepared by the conventional precipitation method generally forms a monoclinic crystal phase after thermal aging [6], rare earth elements have been added to improve the thermal stability of the crystallite itself [26]. In the case of a solid solution formed with these additives, the ZrO 2 crystal phase changes from monoclinic to cubic or tetragonal, hence improving its thermal stability.…”
Section: Thermal Stability Of La-zro 2 In Nd-azlmentioning
confidence: 99%